Women's Silence and Jewish Influence: The Problematic Origins of the Conjectural Emendation on 1 Cor 14.33b-35 - Neutel, Karin B. (New Testament studies, 2019)
This article explores the origins of the conjectural emendation on 1 Cor 14.33b-35, first made in 1863 by Jan Willem Straatman. It shows that Straatman attributes the instruction on women's silence to Jewish influence and bases his view on a reconstruction of early Christianity in which Paul and his Gentile message were opposed by Jewish adversaries. This anti-Jewish tendency persisted in subsequent scholarship and has continued to characterise the understanding of this passage into the twentieth and twenty-first centuries.